Forward Osmosis: Potential use in Desalination and Water Reuse - Altaee, Ali (Journal of Membrane and Separation Technology, 2012)
There has been a recurring interest in using Forward Osmosis (FO) process in water treatment and desalination. Despite the promising results from pilot and bench scale experiments the technology is still not commercialized yet. This is due to the complicated nature of the process which usually involves multiple stages of treatment in addition to the FO membrane process. Unfortunately, most of the recent studies were focused on studying the FO process alone and didn’t provide enough data about the actual cost of the process as whole which includes the osmotic agent regeneration stage/s. This issue resulted in some uncertainties about the total cost of the water treatment by the process. Furthermore, more data are required to evaluate the impact of the osmotic agent losses on the overall cost and efficiency. In case if the draw solution is regenerated by membrane treatment, a suitable membrane should be selected to ensure an optimal salt rejection. For power generation by Pressure Retarded Osmosis (PRO) process, there was an evident progress. However, the process is site specific; i.e. it is dependent of the availability of the draw and donor solution. This suggested that the process is applicable to certain areas but can’t be generalized.